The Chemopreventive Effects of The Combination Between Tea Leaf and Mandarine Peel Extract on Breast Cancer Cell - Ega Hida Prabowo; Rifki Febriansah (Journal of Fundamental and Applied Pharmaceutical Science, 2020)
The number of breast cancer patients is increasing high in the world. This study aims to determine the chemopreventive effect of a combination of ethanolic extracts of tea leaves and mandarin peel in silico and in vitro on T47D breast cancer cells. Extraction by the maceration method used ethanol solvent 70%. The research is an in silico molecular docking utilized software of Autodock Vina to determine the binding affinity of tangeretin compounds and Epigallocatechin gallate (EGCG) on HER-2 protein. The antioxidant test used the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method to determine the antioxidant activity of the combination of tea leaf and mandarine peel (CTM) extract. The in vitro test used the method of 3-(4,5-dimethyltiazol-2-il) -2,5-diphenyltetrazolium bromide (MTT) to determine the value of IC50 fromCTM on T47D breast cancer cells. The result of this study showed that CTM had a vigorous antioxidant activity with an IC50 value of 83 μg/ml. CTM had a weak cytotoxic activity with an IC50 value of 1889 μg/ml. Molecular tethering results of tangeretin and EGCG compounds produced a docking score of -6.6 and -5.0 kcal/mol with docking score proportion consisting of -4.9 kcal/mol of original ligand, -6.1 kcal/mol of doxorubicin and -4.5 kcal/mol of 5-fluorouracil. CTM had potential as a chemopreventive agent based on the robust antioxidant activity data on T47D breast cancer cells and molecular docking on the HER-2 protein.